2019
DOI: 10.1016/j.ebiom.2019.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Rab8 GTPase regulates Klotho-mediated inhibition of cell growth and progression by directly modulating its surface expression in human non-small cell lung cancer

Abstract: Background:The klotho (KL) gene is an anti-aging gene that has recently been shown to also function as a general tumor suppressor. However, there is currently only limited information regarding the potential molecular signals for regulation of Klotho without identifying precise molecular mechanisms or interactions. Methods: We performed a mass spectrometry (MS) assay to screen candidate proteins complexed with Klotho derived from immunoprecipitation in human non-small cell lung cancer (NSCLC) cells, and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…We also found that DEGs were signi cantly enriched in angiogenesis, which is a core hallmark of advanced cancers, especially in LUAD [18][19][20]. Besides, other signi cant GO terms, such as regulation of cell cycle and regulation of small GTPase mediated signal transduction were also related to cancer progression and chemoresistance reported in many studies [21,22]. As shown in Fig.…”
Section: Functional Enrichment Of Dmgssupporting
confidence: 59%
“…We also found that DEGs were signi cantly enriched in angiogenesis, which is a core hallmark of advanced cancers, especially in LUAD [18][19][20]. Besides, other signi cant GO terms, such as regulation of cell cycle and regulation of small GTPase mediated signal transduction were also related to cancer progression and chemoresistance reported in many studies [21,22]. As shown in Fig.…”
Section: Functional Enrichment Of Dmgssupporting
confidence: 59%
“…We also found that DEGs were significantly enriched in angiogenesis, which is a core hallmark of advanced cancers, especially in LUAD [ 18 20 ]. Besides, other significant GO terms, such as regulation of cell cycle and regulation of small GTPase mediated signal transduction were also related to cancer progression and chemoresistance reported in many studies [ 21 , 22 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…KL is down-regulated in lung cancer cells and tissues and even more so in chemotherapy-resistant lung cancer ( Chen et al, 2012 , 2016; Chen B. et al, 2018 ). KL inhibits lung cancer cell proliferation, growth, invasiveness, and migration and fosters apoptosis ( Chen et al, 2010 , 2012 , 2016 , 2019 ; Wang X. et al, 2011 ; Wang et al, 2013 ), effects, at least in part, dependent on IGF-1R/AKT ( Chen et al, 2010 ; Wang et al, 2013 ) and Wnt3a/β-catenin signaling ( Chen et al, 2012 , 2019 ) and on reduced interleukin 6 (IL-6) and IL-8 production ( Chen B. et al, 2018 ). MiR-10b lowers, Ras-related GTPase Ras8 up-regulates KL expression in non–small-cell lung cancer cells ( Huang et al, 2015 ).…”
Section: The Role Of αKlotho In Cancermentioning
confidence: 99%